(3EceGd GdOjf hEJeGe GdfYeI aj EKHGJ GdZjHI hcTa GdMjQIs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3Jbj Hf CejQ eYUhe GdMSjfj Gdbejs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3Qhj Yf GdUGOb LYaQ Hf eMeO YdjgeG GdSdGe ef GdfU Ydi GdbGFe Ydjg GdSdGe (B.. (3hCfg GdKGfj YTQ bGd (B... (3eUfa gPG GdcJGH QMeI Gddg Ydjg MOKfG GdMSjf Hf GMeO Hf EOQjS QVj Gddg Yfg bGd MOKfj CHj Yf CjhH Hf fhM Yf eMeO Hf SfGf Yf UahGf Hf egQGf Yf GdUs
(3BNQgG (B:s
.. (3abGd hYR hef CVd eef GJHY ghGg HZjQ gOi ef Gddg Ef Gddg dG jgOj Gdbhe GdXGdejf hbGd (B: (3aJYSG dge hCVd CYeGdge , hbGd (B: (3cHQ ebJG YfO Gddg hYfO GdPjf BefhG cPdc jWHY Gddg Ydi bdH cd eJcHQ LHGQ(B. (3gPG BNQ GdLRA GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \274s
(3GdCYdGe (B6 \274s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds